METAYOLIVERSE : STRATEGI UNTUK MEMPROMOSIKAN UMKM MELALUI ROBLOX - Istiawan, Gregorius Guardiola; Widyasari, Widyasari (Narada : Jurnal Desain dan Seni, 2023)
The industrial world is increasingly modern with the existence of the virtual metaverse world. This can be seen from the existence of the MSIB program on metaverse implemented by CIAS with the "Metaverse 3D World Creation + Commercialization" program and using Roblox as a medium in visualizing the metaverse. One of the objects of this research is Metayoliverse, one of the program's metaverse projects. The method used in this design is a qualitative method with a Metayoliverse case study approach, observation and SWOT analysis. The methodology in this study began with observing data from Metayoliverse and then proceeding with data analysis using SWOT. In this study, we will analyze the opportunities that can be used on Roblox to promote MSMEs. The results of this study will later show that Roblox has the opportunity to become a medium for promoting MSMEs.